Demystifying Regulating Active Rectifiers for Energy Harvesting Systems: A Tutorial Assisted by Verilog-A Models - Andrea Ballo; Alfio Dario Grasso; Marco Privitera (IEEE Access, 2023)
In this paper the design of regulated active rectifiers (RARs) is addressed, with emphasis on energy harvesting applications. After an insightful overview of the main topologies of RARs, the analytical models are discussed and extended. Then, a data-driven comparison is carried out which, however, does not allows an absolute ranking between the different topologies. Then, a general Verilog-A model of the active rectifier is introduced and extended to simulate and compare the different regulation schemes. Unlike the data-driven comparison, the simulations based on the proposed Verilog-A models allows concluding that the PWM regulation scheme is more suitable for applications requiring an input power lower than about 1mW, whereas the Reconfigurable (1X/0X) is more effective for input power levels in the range 1mW-10mW. The adoption of the developed models allows a huge reduction of the simulation time, equal to 7X for the open loop active rectifier and about 100X for the regulated mode. The accuracy of the proposed model has been extensively verified against transistor-level simulations, showing an error lower than 5% in all conditions. The proposed model is useful during the design phase to select the rectifier topology and control scheme during the design phase and also to reduce the simulation time during pre-silicon verification on complex mixed-signal systems.